2022
DOI: 10.1088/1755-1315/974/1/012111
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on cocoa fermentation techniques to shorten fermentation time

Abstract: Indonesia’s cocoa processing industry has a high demand for fermented cocoa but only about 49% of the fermented cocoa is available. Fermentation is critical because it kills the cotyledons and generates aroma precursors. Indonesian farmers, on the other hand, are hesitant to ferment due to the lengthy fermentation process (6-7 days). The purpose of this study is to conduct a review of several modified cocoa fermentation techniques to determine how they can be used to shorten the fermentation time. The database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Findings from previous studies by Hamidi-Esfahani et al (2019) [ 50 ], He et al (2019) [ 51 ], Calvo et al (2021) [ 52 ] and Rahardjo et al (2022) [ 53 ] collectively highlight the importance of environmental factors in microbial growth and fermentation processes. In the current study, the implementation of CEC had a significant impact in improving the fit of the growth models to the experimental data.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Findings from previous studies by Hamidi-Esfahani et al (2019) [ 50 ], He et al (2019) [ 51 ], Calvo et al (2021) [ 52 ] and Rahardjo et al (2022) [ 53 ] collectively highlight the importance of environmental factors in microbial growth and fermentation processes. In the current study, the implementation of CEC had a significant impact in improving the fit of the growth models to the experimental data.…”
Section: Resultsmentioning
confidence: 95%
“…The study by Rahardjo et al (2022) [ 53 ] showed that controlled fermentation emerged as the most effective method to achieve shorter fermentation times and improve grain quality. This technique not only influenced microbial succession, but also had a significant impact on growth patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some FFs, microbial fermentation of the raw materials is necessary to make them edible. For example, multiple fermentations by a mix of yeasts, AAB and LAB are necessary to digest the pulp covering the cocoa beans and develop chocolate flavour precursors and antioxidants that would otherwise be absent (Goya et al., 2022; Rahardjo et al., 2022).…”
Section: Fermentation As a Sustainable Tool To Ensure Quality And Saf...mentioning
confidence: 99%
“…Over the years, various kinds of processing fruit and its by-product has been studied to increase farmer's income, value development of agro-waste, minimize production losses, or introduce new products to the market (Kurniawan et al, 2018;Nurfaillah, et al, 2018;Guirlanda et al, 2021;Rahardjo, et al, 2022;Tlais et al, 2020).…”
Section: Introductionmentioning
confidence: 99%